Energy Democracy: Advancing Equity in Clean Energy Solutions - Fairchild, Denise; Weinrub, Al; Angarita Horowitz, Diego; Baker, Isaac; Benander, Lynn; Cervas, Strela; Delman, Ben; Giancatarino, Anthony; Huang, Vivian Yi; Johnson, Derrick (Island Press, 2017)
A global energy war is underway.It is man versus nature, fossil fuel versus clean energy, the haves versus the have-nots, and, fundamentally, an extractive economy versus a regenerative economy.